Men, Masculinities and the Modern Career Contemporary and Historical Perspectives - Hoegaerts, Josephine; Aavik, Kadri; Bland, Clarice; Vilhelm Salminen, Janne Tuomas (De Gruyter, 2020)
This book focuses on the multiple and diverse masculinities 'at work'. Spanning both historical approaches to the rise of 'profession' as a marker of masculinity, and critical approaches to the current structures of management, employment and workplace hierarchy, the book questions what role masculinity plays in cultural understandings, affective experiences and mediatised representations of a professional 'career'.